The Uses of Boundaries: Edith Wharton and Place - Virginia RICARD (E-REA)
Edith Wharton’s attitude to place comes as something of a surprise. Usually presented as a cosmopolitan writer, she seems nevertheless to have recognized the usefulness of boundaries. Her characters are often mobile and when they are not, they are trapped by place. Yet homelessness came to seem to Wharton the worst of all fates. In her work, place is necessary to individual growth and fosters a tenderness for others (Lily Bart in The House of Mirth); it contains meanings incommensurate with its surface (“The Look of Paris”); attachment to place is congenial to artistic development (French Ways and Their Meanings); finally, place is never only a prison. It never merely produces what Lionel Trilling called “the morality of inertia”: even “grim” Starkfield in Ethan Frome has redeeming features.